Economic evaluation of a general hospital unit for older people with delirium and dementia (TEAM randomised controlled trial) - Tanajewski, Lukasz; Franklin, Matthew; Gkountouras, Georgios; Berdunov, Vladislav; Harwood, Rowan H.; Goldberg, Sarah E.; Bradshaw, Lucy; Gladman, John R.F.; Elliott, Rachel A. (Public Library of Science, 2015)
Background: One in three hospital acute medical admissions is of an older person with cognitive impairment. Their outcomes are poor and the quality of their care in hospital has been criticised. A specialist unit to care for older people with delirium and dementia (the Medical and Mental Health Unit, MMHU) was developed and then tested in a randomised controlled trial where it delivered significantly higher quality of, and satisfaction with, care, but no significant benefits in terms of health status outcomes at three months.